Islamic Education Values In Early Children - Masganti Sitorus; Mohammad Al Farabi; Harri Wardana (At-Tarbiyat, 2022)
This study aims to analyze the educational process and efforts to instill the values ​​of Islamic education in early childhood, as well as to find the relevance of the importance ​​of Islamic education in early childhood with contemporary Islamic teaching through the study and analysis of the Qur'an sura li 'Imra n verses 33-37. The method used in this research is a qualitative method that was explored through library research. Data collection techniques were carried out by tracing the meaning and content of verses through books of interpretation and various references related to early childhood education content that had relevance to Surah Ali-'Imran verses 33-37, then explained the process of education in early childhood which contained in it, and describes the values ​​of Islamic education that can be learned from the contents of these verses. Furthermore, the data obtained in this study were analyzed using content analysis techniques through the tahlili interpretation approach to reveal the meaning, and main content of the verses studied. The results of the research in this thesis found that the educational process for early childhood contained in the Q.S. li 'Imran verses 33-37 include: (1) being a pious parent figure for the child, (2) naming the child with a good name, (3) praying for the child to avoid the devil's disturbance, (4) choosing a character a pious teacher, (5) creating a good family environment, (6) providing a halal living for children. Meanwhile, efforts to instill the values ​​of Islamic education in children from an early age based on these verses include the values ​​of faith, sharia values, and moral values. The relevance of the value of early childhood education in verse to contemporary Islamic educational institutions is to offer a vision and mission of early childhood education, select good educator figures, and foster spirituality in students in early childhood Islamic educational institutions.